An analysis of Elementary School Students' Errors in Solving Statistics Problems in Online Learning during a Pandemic Period - Iyan Rosita Dewi Nur; Vara Nina Yulian; Laelasari Laelasari (SJME (Supremum Journal of Mathematics Education), 2021)
This study aims to describe the errors made by students and their causal factors in solving statistical problems. This study used descriptive qualitative method. Participants in this study were taken by purposive sampling and obtained 4 selected students. Collecting data in this study using tests and interviews. Based on the results of the research that has been done, it can be concluded that some students make mistakes due to poor understanding of the material, errors in writing flow or systematic answers, error processing skills, basic multiplication skills that are still low, and errors in reading graphs. Factors causing student errors are lack of interest in learning due to online learning that is currently being applied only to providing material and assignments from the teacher and the absence of an explanation of material from the teacher even though online, students inaccuracy, lack of mastery of multiplication which should have been mastered by multiplication basis 4th grade level, do not understand the concept of material, do not understand in operating calculations, and students unfamiliarity in writing conclusions.